Sulfur Oxidation in the Acidophilic Autotrophic Acidithiobacillus spp. - Wang, Rui; Lin, Jian-Qiang; Liu, Xiang-Mei; Pang, Xin; Zhang, Cheng-Jia; Yang, Chun-Long; Gao, Xue-Yan; Lin, Chun-Mao; Li, Ya-Qing; Li, Yang; Lin, Jian-Qun; Chen, Lin-Xu (Frontiers in Microbiology, 2019)
Abstract：Sulfur oxidation is an essential component of the earth’s sulfur cycle. Acidithiobacillus spp. can oxidize various reduced inorganic sulfur compounds (RISCs) with high efficiency to obtain electrons for their autotrophic growth. Strains in this genus have been widely applied in bioleaching and biological desulfurization. Diverse sulfur-metabolic pathways and corresponding regulatory systems have been discovered in these acidophilic sulfur-oxidizing bacteria. The sulfur-metabolic enzymes in Acidithiobacillus spp. can be categorized as elemental sulfur oxidation enzymes (sulfur dioxygenase, sulfur oxygenase reductase and Hdr-like complex), enzymes in thiosulfate oxidation pathways (tetrathionate intermediate thiosulfate oxidation (S4I) pathway, the sulfur oxidation (Sox) system and thiosulfate dehydrogenase), sulfide oxidation enzymes (sulfide:quinone oxidoreductase) and sulfite oxidation pathways/enzymes. The two-component systems (TCSs) are the typical regulation elements for periplasmic thiosulfate metabolism in these autotrophic sulfur-oxidizing bacteria. Examples are RsrS/RsrR responsible for S4I pathway regulation and TspS/TspR for Sox system regulation. The proposal of sulfur metabolic and regulatory models provide new insights and overall understanding of the sulfur-metabolic processes in Acidithiobacillus spp. The future research directions and existing barriers in the bacterial sulfur metabolism are also emphasized here and the breakthroughs in these areas will accelerate the research on the sulfur oxidation in Acidithiobacillus spp. and other sulfur oxidizers.